Strengthening Anti-Money Laundering Frameworks in Sri Lanka: Evaluating Legal Challenges and International Compliance - Wellalage Indira Nanayakkara (New Advances in Business, Management and Economics Vol. 5, 2025)
The criminal practice of money laundering (ML) is increasingly interconnected across various jurisdictions due to its transnational nature. ML poses a significant threat to global financial systems, necessitating coordinated efforts at both national and international levels to combat its adverse effects. Law enforcement agencies within anti-money laundering (AML) frameworks face significant challenges in addressing this issue. It is crucial to comprehensively understand the fundamental principles of ML as a step toward developing effective AML standards. This research examines the impact of ML within the financial sector in Sri Lanka, focusing on strengthening anti-money laundering frameworks. It also explores the proactive measures implemented by financial institutions to mitigate the infiltration of illegal funds, ensuring the provision of secure and reliable financial services to the nation while safeguarding the long-term sustainability of the financial sector, within the context of evaluating legal challenges and international compliance. Methodologically, this research adopts a doctrinal approach to examine and analyze international perspectives and global initiatives to combat ML and evaluates the adherence of Sri Lankan entities to these standards, highlighting areas for improvement. Through a comprehensive analysis of Sri Lanka’s AML efforts, this research aims to provide insights into effective strategies for combating money laundering in similar contexts globally. The study emphasizes the significance of combating ML as a pervasive issue and focuses on Sri Lanka’s experience in addressing ML, examining the effectiveness of its legal frameworks, enforcement mechanisms and compliance with international standards. Despite enacting laws such as the Prevention of Money Laundering Act, Financial Transaction Reporting Act and establishing a Financial Intelligence Unit, Sri Lanka continues to face challenges due to coordination difficulties, political interference, weak monitoring systems and ineffective implementation. This paper analyzes these challenges and explores efforts to enhance the powers of the FIU to strengthen the country’s AML regime. The research finds that to enhance its AML efforts, the country should prioritize continuous evaluation of its systems, use advanced technology for detection and promote international collaboration while promoting public awareness and education on financial crimes. Furthermore, it highlights the establishment of a proactive, multi-faceted strategy and strong local AML system that adheres to global standards for safeguarding Sri Lanka’s economic stability and integrity in the global financial community.